KONTRIBUSI KEKUATAN OTOT LENGAN DENGAN KEMAMPUAN TOLAK PELURU SISWA SMA NEGERI 1 KUBU - Irwasnyah '; Saripin '; Ni Putu Nita Wijayanti (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
ABSTRACT, Background problem in this research is the result of shot put students of SMAN 1 Kubu average did not achieve the target. This problem can be seen from the observation researcher at the learning and assessment in schools, it is suspected because of the strength of the arm muscles. Therefore, the purpose of this study was to determine whether there is a contribution the of the arm muscle strength with shot put ability students of SMAN 1 Kubu. This type of research is correlational comparing the measurement results of two different variables in order to determine the degree of correlation between these variables. As independent variables (X1) is the strength of the arm muscles while the dependent variable (Y) is the shot put ability. Sampling in this study using total sampling technique so that the number of samples 30 male students. The research data was obtained from the results of tests using a expanding dynamometer, and shot put test (5 kg). Based on the research results can be concluded as follows: acquired muscle power arm (X) has a significant corelation with the shot put ability (Y) students SMA Negeri 1 Kubu, characterized by the results obtained by the rhitung 0:55> rtable 0361 with a contribution of 30 %.Keywords : Strength, Arms Muscles, Shot Put